Understanding the molecular origin of the superior toughness of polyamide-6/polyketone blends by solid-state NMR spectroscopy. (27th October 2022) - Zhai, Yuanming; Luo, Yong; Wang, Xiaoyan; Zhang, Chunchun; Deng, Pengchi; Chen, Hanjiao; Zhang, Rongchun; Bao, Ruiying; Zhou, Yicun; Yang, Mingbo; Yang, Wei
Abstract: Polymer blending is a typical and conventional approach for integrating the excellent physical/chemical properties of individual polymer components. Specifically, the mechanical toughness and strength of polyamide-6 (PA6)/polyketone (PK) blend are substantially enhanced compared to either PA6 or PK individual component. Nevertheless, there are few atomic-level insights into such mechanical property enhancement. In this study, solid-state nuclear magnetic resonance (NMR) is utilized as a main tool to understand the molecular origin of the mechanical enhancement of PA6/PK blends. The proton relaxation times are used to evaluate the miscibility and domain sizes in PA6/PK blends, and to determine the crystallinity of each component, where both conventional DSC and WAXD experiments fail because of similar crystallization/melting behaviors of PA6 and PK components. 2D 1 H– 13 C WISE (wideline separation) and HETCOR (heteronuclear correlation) solid-state NMR spectroscopy were performed to further reveal the nano-heterogeneous structures and hydrogen bonding interactions in PA6/PK blend. With further combination with FTIR and SEM results, the previous characteristic morphological model for elucidating the toughening mechanism for PA6/PK blends is refuted, and it is proposed that the superior performance of PA6/PK blend is resulted from the synergistic effects of enhanced interfacial adhesion and interconnected interphase percolated in the bulk PA6/PK blends via hydrogen bonds. We envisage the detailed molecular level insights provided by solid-state NMR spectroscopy could assist in the bottom-up design of high performance polymer blend materials. Graphical abstract: Image 1 Highlights: The locations of hydrogen bonding between PA6 and PK are precisely determined. The strength of hydrogen bonding interactions is semi-quantitatively characterized. A complementary approach for studying crystallization of polymer blends is provided. Insights into the toughening mechanism via solid-state NMR techniques are obtained.